AeU organises 'It's Time to Reconnect' event for alumni - New, Sarawak Tribune (New Sarawak Tribune, 2016)
AEU's Alumni High Tea Reunion event theme, "It's Time to Reconnect" was held on April 9 at Royale Bintang Hotel Kuala Lumpur. The event was graced by Professor Dato' Dr Ansary Ahmed, President and Chief Executive Officer of AeU and Professor Prof Dr Hairudin Harun, deputy president. Others who attended are Deans, Directors and Senate Members.